Analysis of Groundwater Quality in Rental Flats use Physical and Chemical Parameters - Mohammad Agus Prayitno; Putut Marwoto; Sigit Priyatmoko; Deni Ebit Nugroho (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to determine the physical and chemical quality of the groundwater in the Jerakah flats area and to determine the feasibility of the water as drinking water. This research was physically carried out by analyzing groundwater samples from the rented flats of the Jerakah sub-district based on the physical parameters of the air, including taste, color, smell, temperature, turbidity, and dissolved solids (TDS) as well as chemical parameters consisting of the degree of acidity. (pH), Nitrate Content (NO3-), Nitrite (NO2-), Hardness (CaCO3), Iron (Fe), Lead (Pb), Manganese (Mn), Zinc (Zn), Sulfate (SO42-), Cadmium (Cd), and Chromium (Cr). The results showed that the groundwater in the Jerakah flats had a normal pH, colorless, tasteless, odorless, low turbidity, and high dissolved solids (TDS). The levels of iron (Fe), manganese (Mn), chromium (Cr), zinc (Zn), cadmium (Cd), lead (Pb), and hardness are below the maximum hygienic sanitary limits. Manganese (Mn), Cadmium (Mn), Lead (Pb) levels exceed the maximum limit for drinking water. The groundwater in the Jerakah flat is suitable for use for hygienic sanitation, such as bathing and washing, but not suitable for drinking.